Modified indirect fluorescent-antibody test for aspergillosis. - Gordon, M A (1977)
Diffuse fluorescence in an indirect fluorescent-antibody test for antibody to Aspergillus fumigatus was eliminated by using germlings, rather than hyphae, as antigen. The modified method yielded diagnostic titers larger than or equal to 1:32 in 24 of 25 known cases, was highly specific, and showed good correlation with clinical status and results of immunodiffusion. This technique, which uses the germling antigen, inactivation of test serum at 59 +/- 1 degrees C, and anti-immunoglobulin G conjugate, is a sensitive, specific, and reliable quantitative indicator of aspergillosis and is useful in following the course of the disease.